Why the cheetah cheats : and other mysteries of the natural world - Smith, Lewis (Great Britain : Papadakis Pub., 2009)
Smith brings to vivid life 100 cutting-edge research projects that have yielded some remarkable answers to previously unexplained mysteries of the natural world
Keywords: Animals -- Miscellanea; Animals -- Habitations; Animals -- Effect of pollution on; Animals -- Effect of global warming on; Animal behavior; Extinct animals